Litter Production Pattern in an Acacia tortilis Based Silvopastoral System in the Dry Tropics - Roy, M. M.; Nigam, Gaura V. (Indian Forester, 2001)
Investigations on the pattern of litter production in an Acacia tortilis (> 12 years) based silvopastoral systems system, raised on degraded land in semi-arid conditions of Jhansi (India) have shown that average litter production was 4.72 t/ha. The leaves contributed about 62.4 per cent followed by reproductive structures (23.02%) and twigs (14.58%). Higher litter production was recorded in the drier months of May (119.92 g/m2) and June (88.32 g/m2) and April (72.35 g/m2). During rainy season (July-October) there was almost no litter production. There existed a significant negative correlation between average minimum (r=0.87) and maximum temperature (r=0.85). During the litter production season significant positive correlation was found with amount of rainfall (r=0.90).